2016
DOI: 10.3390/ijms17050678
|View full text |Cite
|
Sign up to set email alerts
|

SARS Coronavirus Papain-Like Protease Inhibits the TLR7 Signaling Pathway through Removing Lys63-Linked Polyubiquitination of TRAF3 and TRAF6

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) papain-like protease (PLPro) reportedly inhibits the production of type I interferons (IFNs) and pro-inflammatory cytokines in Toll-like receptor 3 (TLR3) and retinoic acid-inducible gene 1 (RIG-I) pathways. The study investigated the inhibitory effect and its antagonistic mechanism of SARS-CoV PLPro on TLR7-mediated cytokine production. TLR7 agonist (imiquimod (IMQ)) concentration-dependently induced activation of ISRE-, NF-κB- and AP-1-luciferase repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
137
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 27 publications
1
137
0
3
Order By: Relevance
“…The SARS‐CoV PL pro removes Lys63‐linked ubiquitin (Ub) chains from TRAF3 and TRAF6 to reduce the TLR7‐mediated immune signaling . Furthermore, the SARS‐CoV PL pro cannot remove Lys48‐linked Ub chains from TRAF3 and TRAF6 according to a western blot assay . This is at variance with an in vitro study that demonstrated that SARS‐CoV PL pro prefers to process Lys48‐ over Lys63‐linked polyUb chains .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 90%
See 1 more Smart Citation
“…The SARS‐CoV PL pro removes Lys63‐linked ubiquitin (Ub) chains from TRAF3 and TRAF6 to reduce the TLR7‐mediated immune signaling . Furthermore, the SARS‐CoV PL pro cannot remove Lys48‐linked Ub chains from TRAF3 and TRAF6 according to a western blot assay . This is at variance with an in vitro study that demonstrated that SARS‐CoV PL pro prefers to process Lys48‐ over Lys63‐linked polyUb chains .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 90%
“…The SARS‐CoV PL pro removes Lys63‐linked ubiquitin (Ub) chains from TRAF3 and TRAF6 to reduce the TLR7‐mediated immune signaling . Furthermore, the SARS‐CoV PL pro cannot remove Lys48‐linked Ub chains from TRAF3 and TRAF6 according to a western blot assay .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immunementioning
confidence: 99%
“…SARS-CoV PL2 pro plus TM can also physically interact with the STING-TRAF3-TBK1 complex and remove the ubiquitins from ubiquitinated RIG-I, STING, TRAF3, TBK1, as well as IRF3 . In 2016, it was reported that the SARS-CoV PL2 pro can inhibit the Toll-like receptor 7 (TLR7)-mediated type-I IFN response and the NF-κB pathway by removing the Lys63-linked polyUb chain from TRAF3 and TRAF6 (upstream regulators of IRF3 and NF-κB;Li et al, 2016b). Interestingly, the SARS-CoV PL2 pro only removes the Lys63-but not the Lys48-linked polyUb chain from TRAF3 and TRAF6 in vivo (Li et al, 2016b).…”
Section: Papain-like Protease 2 (Pl2 Pro )mentioning
confidence: 99%
“…In 2016, it was reported that the SARS-CoV PL2 pro can inhibit the Toll-like receptor 7 (TLR7)-mediated type-I IFN response and the NF-κB pathway by removing the Lys63-linked polyUb chain from TRAF3 and TRAF6 (upstream regulators of IRF3 and NF-κB;Li et al, 2016b). Interestingly, the SARS-CoV PL2 pro only removes the Lys63-but not the Lys48-linked polyUb chain from TRAF3 and TRAF6 in vivo (Li et al, 2016b). On the other hand, Báez-Santos et al (2014) and Békés et al (2015Békés et al ( , 2016 have shown that SARS-CoV PL2 pro prefers to digest Lys48over Lys63-linked polyUb chains in vitro (see above).…”
Section: Papain-like Protease 2 (Pl2 Pro )mentioning
confidence: 99%
“…PLpro, a de-ubiquitinating/de-ISGylating enzyme (Barretto et al, 2005;Ratia et al, 2006), has the antagonistic activities of Type I interferon (IFN) via blocking IRF-3 and ERK1 phosphorylation, preventing the IκBα degradation, and de-ubiquitinating the STING-TRAF3-TBK1 complex (Li et al, 2011;Frieman et al, 2009;Sun et al, 2012). Recently, PLpro shows the inhibitory effect on Tolllike receptor 7 (TLR7) mediated cytokine production through removing Lys63-linked ubiquitin chains of TRAF3 and TRAF6 (Li et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%